The afterlife of Apuleius - Bistagne, Florence; Boidin, Carole; Mouren, Raphaële (Bulletin of the Institute of Classical Studies. Supplement ;, 2021)
Preface and acknowledgements / F. Bistagne, C. Boidin, and R. Mouren -- Apuleius' travels: historical and geographical diffusion -- The medieval Ass: re-evaluating the reception of Apuleius in the High Middle Ages / Robert H.F. Carver -- The White Goddess in Mexico: Apuleius, Isis, and the Virgin of Guadalupe in Latin, Spanish, and Nahuatl sources / Andrew Laird -- The Ass goes east: Apuleius and orientalism / Carole Boidin -- The afterlife of Psyche -- How to tell the story of Cupid and Psyche: from Fulgentius to Galeotto Del Corretto / Julia Haig Gaisser -- Psyche's textual journey from Apuleius to Boccaccio and Petrarch / Igor Candido -- An Apuleian masque? Thomas Heywood's Love's Mistress (1634) / Stephen Harrison -- Echoes of Apuleius' novel in Mary Tighe's Psyche: Romantic imagination and self-fashioning / Regine May -- A fashionable model? Formal patterns and literary values -- Apuleius and Martianus Capella: reception, pedagogy, and the dialectics of canon / Ahuvia Kahane.